Comparison of methods for obtaining serum opacity factor from group A streptococci. - Rehder, C D (1995)
Streptococcal serum opacity factor (OF) is an important type-specific strain marker produced by certain serotypes of group A streptococci (GAS). The accurate determination of OF production and subsequent serotyping of a strain require a reliable method for extracting OF. Traditional OF extraction methods have utilized either culture supernatants or Lancefield HCl extracts. However, these methods do not consistently yield adequate amounts of OF for accurate characterization of all strains. To improve the accuracy of OF utilized and found to be reproducibly sensitive and suitable for routine laboratory use. A total of 3,014 GAS were examined for OF production by each of the three methods. The SDS extraction method accurately detected OF in all 1,302 OF-producing strains, whereas the HCl extraction method correctly identified 1,202 (92%) and the supernatant method identified only 1,141 (88%) of the isolates. When the 1,302 OF-producing strains were further evaluated to determine if sufficient OF had been extracted for reliable OF serotyping, 1,147 (88%) of the SDS extracts were found to be satisfying compared with 1,081 (83%) of the HCl extracts and only 936 (72%) of the culture supernatants. The improved ability to characterize OF-producing strains by using SDS was statistically significant compared with the results obtained by the other two techniques. This technique offers distinct advantages, including enhanced detection of OF production and improved reliability of serotyping OF-producing GAS.